ACCURACY OF CBCT IN MANDIBULAR CONDYLE VOLUMETRIC AND SURFACE MEASUREMENT: LITERATURE REVIEW - Shukur, Fahad; Radhi, Sarab; Alsarav, Rusul (Journal of Medical Genetics and Clinical Biology, 2024)
The purpose of this review is to evaluate the accuracy and reliability of cone beam computed tomography (CBCT) in in the measurement and diagnosis of mandibular condyle morphology, in comparison to other diagnostic devices. The design and method In order to achieve our study, we searched several databases, including Google Scholar, PubMed, and Scopus. We only considered studies published between 2005 and 2023. Our review was focused on clinical trials, meta-analysis, article reviews, and randomized controlled trials. The exclusion criteria included patients with certain medical conditions, jaw abnormalities, jaw fractures, and animal experiments. The studies we analyzed had to address one specific question: What is the diagnostic accuracy of Cone Beam Computed Tomography (CBCT) compared to conventional tomography? conclusion: CBCT has become a cost- and dose-effective alternative to CT for examining the condyle and also TMJs. This imaging method is better than conventional radiographic methods and MRI in assessing osseous TMJ abnormalities, despite being more sensitive to motion artifacts. In addition, CBCT-MRI fused images can significantly improve the reliability of observers in determining anterior disc displacement and bone changes of the TMJ. This technology can also be utilized to improve diagnostic efficacy, especially for inexperienced residents.